PUBLIC PARTICIPATION AND INTEREST IN THE PROCESS OF LATVIAN STATE ADMINISTRATION - Mirlina, Liga (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
Democratic state administration needs interaction with the public, which requires not only government communication with the public but also the public interest and understanding in the political and public administration processes. The task of public administration is to create a legal and institutional framework and mechanisms for public participation, while NGOs and the general public need civil competency to use the opportunities of public participation. Analysing the Latvian government's communication activities related to public participation and public awareness, the aim of this paper is to examine the level of participation of different social groups and the impact of their awareness on it. Within the framework of the research, the following methods have been used: analysis of normative documents, statistics on the implementation of the Memorandum of cooperation between the government and non-governmental organizations, interviews with experts from NGOs and state administration, focus group discussions with young people. Analysing legal documents and statistics on the involvement of NGOs, public participation platforms and their use have been evaluated. Based on the views of NGOs and state administration experts, there are certain factors that influence the level of public participation and public awareness. Focus group discussions with young people have identified their awareness and interest in public administration processes as well as their civic participation. The research study found that the state administration has created a variety of platforms for the involvement of NGOs in decision-making processes and an increase in the participation of NGOs. By choosing young people as one of the social groups of society, it can be concluded that information about public participation does not reach the general public, thus it has little effect on the formation of the general public's awareness and the level of participation.